PERBAIKAN HISTOLOGIS PUSAT LEARNING AND MEMORY DI HIPOKAMPUS OTAK SETELAH PERLAKUAN SUPLEMEN DAGING IKAN GABUS (CHANNA STRIATA) DALAM PAKAN: KAJIAN IN VIVO PADA TIKUS WISTAR PASCA STRES - Reynato Wijaya Saputra; S Sunarno; Siti Muflichatun Mardiati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Background: Stress due to lack of feed that followed excessive activity is a trigger factor learning and memory disorder center in the hippocampus. Cornu ammonis (CA3 and CA1) in the hippocampus is a structure that is central to learning and memory. Complete nutrient content of feed is supporting the regeneration of the structure of CA3 and CA1 in the hippocampus impaired due to stress . This research was conducted to obtain a histological improvement layers of CA3 and CA1 hippocampus in the rat brain after supplementation with snakehead fish meat in the feed of post-stress.Design and Method: This study uses a completely randomized design consisting of 6 treatments with 4 replications. Test animals used were male Wistar rats. Treatments, including P0: control, namely Wistar rats were conditioned to stress during the six days that followed the feeding without supplementation of snakehead fish meat for 14 days; P1, P2, P3, and P4, respectively Wistar rats were conditioned stress followed by supplemental feeding snakehead fish meat 5%, 10%, 15% and 20%. The research variables measured the thickness of the layer of CA3 and CA1. Data were analyzed using Analysis of Variance (ANOVA) at the level of 95% and continued with Duncan test with 95% significance level .Result: Supplemental feeding with snakehead fish meat as much as 15% during 14 days in Wistar rats after stress gives the best effect on the improvement of CA3 and CA1 layer of the hippocampus, respectively 53.60 μm2 (17.49%) and 46.31 μm2 (78,32%), better than the control.Conclusion: Feeding the snake head fish meat supplementation for 14 days in Wistar rats after stress can improve layer CA3 and CA1 in the hippocampus of the brain. Recommended snake head fish meat can be used as a feed supplement to improve the structure of CA3 and CA1 in the hippocampus and very good to support the learning and memory functions of the brain. Keywords: snakehead fish meat, Channa striata, cornu ammonis, supplementation, hippocampus, learning and memory